The Basic Characteristics of the Pentraxin Family and Their Functions in Tumor Progression - Wang, Zeyu; Wang, Xing; Zou, Hecun; Dai, Ziyu; Feng, Songshan; Zhang, Mingyu; Xiao, Gelei; Liu, Zhixiong; Cheng, Quan (Frontiers in Immunology, 2020)
The pentraxin family is a superfamily consist of proteins with the same domain called the pentraxin domain at C-terminal. This family is divided into the short pentraxins (C-reactive protein and amyloid P component serum) and the long pentraxins (neuronal pentraxin 1, neuronal pentraxin 2, neuronal pentraxin receptor, pentraxin 3 and pentraxin 4), and each of them shares the similar structure, a pentameric complexes arranged in discoid shape. Previously researches revealed the functions of different family members such as most of the family members involve in human innate immunity, amyloid P component serum connects to amyloidosis disease. It is well known that inflammation is bound closely with tumor progression and the pentraxin family might participate in tumor progression. Therefore, we summarized the basic characteristics of this family, their function and their relationship with tumor in this review. And we discovered that the ways how this family affects tumor progression are different and this difference is highly connected with their unique structure.